2015
DOI: 10.1186/s12885-015-1709-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of programmed cell death 10 is associated with tumor cell proliferation, hyperangiogenesis and peritumoral edema in human glioblastoma

Abstract: BackgroundNeovascularization and peritumoral edema are hallmarks of glioblastoma (GBM). Programmed cell death 10 (PDCD10) plays a pivotal role in regulating apoptosis, neoangiogenesis and vessel permeability and is implicated in certain tumor signaling pathways. However, little is known about PDCD10 in GBM. We aimed to investigate the expression pattern of PDCD10 and to identify the association of its expression with some molecular and clinical parameters in human GBM.MethodsmRNA and protein expression of PDCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
(62 reference statements)
5
25
0
Order By: Relevance
“…This observation was in accordance with previous findings that revealed that silencing PDCD10 could inhibit the proliferation of endothelial cells (32). Lambertz et al (33) proposed that PDCD10 potentially participated in tumor proliferation, apoptosis, hyper-angiogenesis and peritumoral edema in human glioblastoma. In addition, downregulation of PDCD10 inhibited tumor cell proliferation (33).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation was in accordance with previous findings that revealed that silencing PDCD10 could inhibit the proliferation of endothelial cells (32). Lambertz et al (33) proposed that PDCD10 potentially participated in tumor proliferation, apoptosis, hyper-angiogenesis and peritumoral edema in human glioblastoma. In addition, downregulation of PDCD10 inhibited tumor cell proliferation (33).…”
Section: Discussionsupporting
confidence: 93%
“…Lambertz et al (33) proposed that PDCD10 potentially participated in tumor proliferation, apoptosis, hyper-angiogenesis and peritumoral edema in human glioblastoma. In addition, downregulation of PDCD10 inhibited tumor cell proliferation (33). In addition to the effect on proliferation, previous studies indicated a positive correlation between Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Total protein extraction and Western blot were performed according to the previously established protocols . The following primary antibodies were used: rabbit anti‐Dll4 (1:1000; Cell Signaling Technology, Frankfurt, Germany), rabbit anti‐cleaved Notch1 (1:500; Cell Signaling Technology), goat anti‐cleaved Notch4 (1:200; Santa Cruz Biotechnology, Sant Cruz, CA, USA), rabbit anti‐Hey1 (1:200; Abcam, Cambridge, UK), mouse anti‐PCNA (1:500; Dako, Hamburg, Germany), rabbit anti‐VEGF (1:500; Santa Cruz Biotechnology), rabbit anti‐CXCR4 (1:500; Abcam), mouse anti‐p‐Akt (Ser473) (1:1000; Cell Signaling Technology), rabbit anti‐p‐Erk1/2 (Thr202/Tyr204 for P‐Erk1; Thr185/Tyr187 for P‐Erk2; 1:1000; Cell Signaling Technology) and rabbit anti‐GAPDH (1:1000; Cell Signaling Technology) as reference protein.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein extraction and Western blot were performed according to the previously established protocols. 22 The following primary antibodies were used: rabbit anti-Dll4 (1:1000; Cell Signaling Technology, Frankfurt, Germany), rabbit anti-…”
Section: Western Blotmentioning
confidence: 99%
“…Phosphorylated PI3K/Akt inhibits pro-apoptotic substrates, such as CHOP and p-JNK, while it promotes the anti-apoptotic substrate Bcl-2 (21). Recent evidence suggests that PDCD10 is associated with the activation of Akt signaling protein (22). The current study found that miR-613 significantly increased the level of p-Akt and Bcl-2 expression; when miR-613 was overexpressed, however, the level of expression of the pro-apoptotic proteins CHOP and p-JNK decreased significantly.…”
Section: Discussionmentioning
confidence: 99%